Scythian motifs and imagery in traditional and contemporary jewelry art in Tuva - Ayzhy, Zhanna E.; Nan-Khoo, Yana N. (The New Research of Tuva, 2021)
The article examines a number of features of traditional art of jewelry art of Tuva. Also analyzed are the works of contemporary jewelry artists who explore the iconography and follow the style of the Scythian-Siberian animal style. The article looks at the most widespread types of Tuvan jewelry of the turn of the 20th century — earrings, signet rings, ornamental best plates and braid decorations, which are preserved and exhibited at the National Museum of the Republic of Tuva (1131 items all in all). The authors conclude that little continuity can be traced between early nomadic art and that of late 19th and early 20th century. Among the surviving traditions are the koshkar myiyzy zoomorphic ornament (transformed to feature a floral ornament) and the chechektep plant motif as a multifoil rosette, both stemming back to the art of ancient Scythians. Since the 2000s, the Scythian-Siberian style has seen a conscious revival, largely due to the opening of a permanent exposition at the National Museum which familiarized jewellers, as well as other visitors, with the treasures of the royal couple and the aristocracy from Arzhan and Arzhan II mounds. Of contemporary Tuvan artists, a special focus is made on Venera Nikulina, Aibes Olchei, and Yelena Sedip. Their works of silver, gold, beads and other materials organically combine ethnic Tuvan stylistic traditions and daring attempts of applying the Scythian animal style to the contemporary trends in jewelry art (as they, e.g., appear in the bead art of Yelena Sedip). Their jewelry is found to be part of a new trend in the art of contemporary Tuva, the trend which provides a new interpretation of the ancient imagery and motifs.